2016
DOI: 10.1080/21501203.2015.1136708
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of endophytic fungi of the Sri Lankan aquatic plantNymphaea nouchaliand chaetoglobosin A and C, produced by the endophytic fungusChaetomium globosum

Abstract: Twenty distinct endophytic fungi were isolated from the surface-sterilized plant parts of Nymphaea nouchali and were identified using morphological and molecular techniques. At 300 µg/disc concentration, eight of the 20 fungal extracts exhibited antimicrobial activities against Staphylococcus aureus (ATCC 25923) and Bacillus cereus (ATCC 11778) while two within the eight showed activity against Pseudomonas aeruginosa (ATCC 9027) and Escherichia coli (ATCC 35218). Furthermore, investigation of the crude extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Similar, standardized endophytic fungal isolation by imprint method has been used in Ficus pumila, Basella rubra and Camellia sinensis to evaluate the effectiveness of surface sterilization of the plant materials (Rakshith et al 2013;Hema et al 2015;Guo et al 2016). The results of the present study are in agreement with the findings of Rao et al (2015), where a single endophytic fungus Gliomastix polychrome was isolated from surface-sterilized bark of Combretum latifolium, while there are also reports of isolation of more than one endophytic fungi from Nymphaea nouchali (Dissanayake et al 2016). Our fungal isolate emerging from the tissue of the inoculated plant part was identified as Aspergillus sp.…”
Section: Isolation and Identification Of Endophytic Fungisupporting
confidence: 83%
See 2 more Smart Citations
“…Similar, standardized endophytic fungal isolation by imprint method has been used in Ficus pumila, Basella rubra and Camellia sinensis to evaluate the effectiveness of surface sterilization of the plant materials (Rakshith et al 2013;Hema et al 2015;Guo et al 2016). The results of the present study are in agreement with the findings of Rao et al (2015), where a single endophytic fungus Gliomastix polychrome was isolated from surface-sterilized bark of Combretum latifolium, while there are also reports of isolation of more than one endophytic fungi from Nymphaea nouchali (Dissanayake et al 2016). Our fungal isolate emerging from the tissue of the inoculated plant part was identified as Aspergillus sp.…”
Section: Isolation and Identification Of Endophytic Fungisupporting
confidence: 83%
“…Likewise, ethyl acetate extract of endophytic fungi from Bacopa monnieri displayed antimicrobial activity against B. subtilis, P. aeruginosa, S. typhimurium, E. coli, K. pneumonia and S. aureus with MIC of 10-100 lg/mL (Katoch et al 2014). Also, Ratnaweera et al (2015) and Dissanayake et al (2016) have reported that endophytic fungi Fusarium sp. and Chaetomium globosum isolated from Opuntia dillenii and N. nouchali, respectively, offered antibacterial activity with MIC ranging from 8 to 32 lg/mL against B. subtilis, S. aureus and methicillin-resistant S. aureus.…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal strain was cultured in PDA at a room temperature for 3 days. Mycelium of fungus was scraped and the isolation of genomic DNA from the mycelia of fungal isolate was carried out according to the published protocol as previously reported ( Dissanayake et al, 2016 ). The ITS region of the isolated genomic DNA was amplified by polymerase chain reaction (PCR) using the forward primer ITS1 and the reverse primer ITS4 under the conditions.…”
Section: Methodsmentioning
confidence: 99%
“…An endophytic fungus of Nymphaea nouchali (Sri Lanka) called Chaetomium globosum, led to the isolation of cytochalasans, chaetoglobosin A and C from the crude extract of the two distinct fungi. The compounds showed antibacterial activities against test microorganisms, and chaetoglobosin A (1) inhibited MRSA ATCC 33591 and S. aureus ATCC 43300 at MIC values of 32 and 32 µg/mL, respectively [88].…”
Section: Marine Alga-associated Fungimentioning
confidence: 98%